Neural Underpinnings of Distortions in the Experience of Time Across Senses - Harrington, Deborah L.; Castillo, Gabriel N.; Fong, Christopher H.; Reed, Jason D. (Frontiers in Integrative Neuroscience, 2011)
Auditory signals (A) are perceived as lasting longer than visual signals (V) of the same physical duration when they are compared together. Despite considerable debate about how this illusion arises psychologically, the neural underpinnings have not been studied. We used functional magnetic resonance imaging (fMRI) to investigate the neural bases of audiovisual temporal distortions and more generally, intersensory timing. Adults underwent fMRI while judging the relative duration of successively presented standard interval–comparison interval (CI) pairs, which were unimodal (A–A, V–V) or crossmodal (V–A, A–V). Mechanisms of time dilation and compression were identified by comparing the two crossmodal pairs. Mechanisms of intersensory timing were identified by comparing the unimodal and crossmodal conditions. The behavioral results showed that auditory CIs were perceived as lasting longer than visual CIs. There were three novel fMRI results. First, time dilation and compression were distinguished by differential activation of higher-sensory areas (superior temporal, posterior insula, middle occipital), which typically showed stronger effective connectivity when time was dilated (V–A). Second, when time was compressed (A–V) activation was greater in frontal cognitive-control centers, which guide decision making. These areas did not exhibit effective connectivity. Third, intrasensory timing was distinguished from intersensory timing partly by decreased striatal and increased superior parietal activation. These regions showed stronger connectivity with visual, memory, and cognitive-control centers during intersensory timing. Altogether, the results indicate that time dilation and compression arise from the connectivity strength of higher-sensory systems with other areas. Conversely, more extensive network interactions are needed with core timing (striatum) and attention (superior parietal) centers to integrate time codes for intersensory signals.